The pre-Socratics, with an Epicurean nod and an epilogue Homeric (XXI Century. Spanish Literature and Culture, 2010)
This essay is a reflection on the pre-Socratics and their well-known imputation to “Know thyself”; in other words, the search for ontological origins in western philosophy. It also explores questions of self-knowledge, univocal truth, practical reason, knowledge, and destiny.
Keywords: Vicente Gallego; Pre-Socratics; self-knowledge; destiny